2006
DOI: 10.1128/mcb.02473-05
|View full text |Cite
|
Sign up to set email alerts
|

The Scaffold Protein Cybr Is Required for Cytokine-Modulated Trafficking of Leukocytes In Vivo

Abstract: Trafficking and cell adhesion are key properties of cells of the immune system. However, the molecular pathways that control these cellular behaviors are still poorly understood. Cybr is a scaffold protein highly expressed in the hematopoietic/immune system whose physiological role is still unknown. In vitro studies have shown it regulates LFA-1, a crucial molecule in lymphocyte attachment and migration. Cybr also binds cytohesin-1, a guanine nucleotide exchange factor for the ARF GTPases, which affects actin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 31 publications
2
35
1
Order By: Relevance
“…Lymphocytes show a deficit in their trafficking behaviour and the CD8-mediated immune response to Moloney murine sarcoma virus (M-MSV) is delayed significantly. This is attributed to the impaired trafficking capacity of lymphocytes (Coppola et al, 2006), but is also in accordance with the finding that human dendritc cells silenced for CYTIP show a reduced stimulatory capacity for antigen-specific CD8 positive T-cells (Hofer et al, 2006). With the latter mouse model Watford and colleagues, in accordance with the first mouse model, found no effect of lack of Cybr on the development of the immune system.…”
Section: Yand In Vivosupporting
confidence: 58%
See 1 more Smart Citation
“…Lymphocytes show a deficit in their trafficking behaviour and the CD8-mediated immune response to Moloney murine sarcoma virus (M-MSV) is delayed significantly. This is attributed to the impaired trafficking capacity of lymphocytes (Coppola et al, 2006), but is also in accordance with the finding that human dendritc cells silenced for CYTIP show a reduced stimulatory capacity for antigen-specific CD8 positive T-cells (Hofer et al, 2006). With the latter mouse model Watford and colleagues, in accordance with the first mouse model, found no effect of lack of Cybr on the development of the immune system.…”
Section: Yand In Vivosupporting
confidence: 58%
“…For in vivo characterization of the multinamed molecule two Cybr-deficient mice were created, one by the removal of exon 1 using the cre-lox system (Coppola et al, 2006), the other by replacing parts of exon 2 and exon 3 by enhanced EGFP-encoding sequence (Watford et al, 2006). Using the first mouse model, Coppola and colleagues found that Cybr deletion does not seem to affect the development of the immune system.…”
Section: Yand In Vivomentioning
confidence: 99%
“…Subsequently, the complex translocates from the plasma membrane to the cytosol, thereby interrupting the activation of LFA-1. 14 Recently, it was shown that CYTIP regulates leukocyte trafficking 15 and the adherence of DCs to fibronectin 16 as well as T-cell detachment and T-cell priming. 16,17 Herpes simplex virus type 1 (HSV-1) is the prototypic member of the large and diverse family of herpesviridae, including several human pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Cytip-deficient mice [7] were kindly provided by Antonio Rosato (Department of Oncology and Surgical Sciences, University of Padova, Italy).…”
Section: Methodsmentioning
confidence: 99%